He-Ne Laser Seed Treatment Improves the Nutraceutical Metabolic Pool of Sunflowers and Provides Better Tolerance Against Water Deficit - Mahmood, Saqib; Afzal, Beenish; Perveen, Shagufta; Wahid, Abdul; Azeem, Muhammad; Iqbal, Naeem (Frontiers in Plant Science, 2021)
Water-scarce areas are continually increasing worldwide. This factor reduces the quantity and quality of crops produced in affected areas. Physical seed treatments are considered economical and ecofriendly solutions for such problems. It was hypothesized that a moderately drought-tolerant crop grown from seeds treated with a He-Ne laser utilizes water-limited conditions better than plants grown from untreated seeds. A field study was conducted, growing a moderately drought tolerant crop (sunflower) with supportive seed treatment (He-Ne laser treatment at 300 mJ) for 0, 1, 2, and 3 min. Thirty-day-old plants were subjected to two irrigation conditions: 100% (normal) and 50% (water stress). Harvesting was done at flowering (60-day-old plants) at full maturity. The sunflowers maintained growth and yield under water limitation with a reduced achene number. At 50%, irrigation, there was a reduction in chlorophyll a, a+b and a/b; catalase activity; soluble sugars; and anthocyanin, alongside elevated proline. The improved chlorophyll a, a+b and a/b; metabolisable energy; nutritional value; and yield in the plants grown from He-Ne-laser-treated seeds support our hypothesis. Seeds with 2-min exposure to a He-Ne laser performed best regarding leaf area; leaf number; leaf biomass; chlorophyll a, a+b and a/b; per cent oil yield; 50-achene weight; achene weight per plant; carotenoid content; and total soluble phenolic compound content. Thereafter, the leaves from the best performing level of treatment (2 min) were subjected to high-performance-liquid-chromatography-based phenolic profiling and gas-chromatography-based fatty acid profiling of the oil yield. The He-Ne laser treatment led to the accumulation of nutraceutical phenolic compounds and improved the unsaturated-to-saturated fatty acid ratio of the oil. In conclusion, 2-min He-Ne laser seed treatment could be the best strategy to improve the yield and nutritional value of sunflowers grown in water-limited areas.